1991
DOI: 10.1143/jjap.30.2542
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bulk Orderings and Anchoring Structures of Liquid Crystals Studied by Scanning Tunneling Microscopy

Abstract: PACS. 21.65 -Nuclear matter.PACS. 21.10R -Collective structure in levels (inc. rotational bands). PACS. 21.60E -Collective models. PACS. 23.20 -Electromagnetic transitions.Abstract. -Rotational states and electromagnetic transitions among them are studied in a deformed even mass nucleus by a microscopic calculation. Spectra, E2 and M1 matrix elements among different bands are studied by diagonalization-after-projection. The Z Z -1 E 2 and M1 transitions among the p a s t states show a marked dependence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…The Cr and Au electrodes were deposited to a thickness of 2 and 40 nm, respectively. LC molecules were then spin‐coated onto the film at 6000 rpm over 40 s. Finally, regions within the large graphene film that displayed the desired properties (three regions with varying degrees of domains) were carefully selected by observing the self‐assembled liquid crystals (5CB) on the graphene surfaces using polarized optical microscopy (POM), which yielded colored optical birefringence images of the graphene surface covered with the LC molecules due to molecular interactions between the LC molecules and graphene structures . The color differences in the birefringence images could be readily used to identify the sizes and boundaries of the graphene domains .…”
mentioning
confidence: 99%
“…The Cr and Au electrodes were deposited to a thickness of 2 and 40 nm, respectively. LC molecules were then spin‐coated onto the film at 6000 rpm over 40 s. Finally, regions within the large graphene film that displayed the desired properties (three regions with varying degrees of domains) were carefully selected by observing the self‐assembled liquid crystals (5CB) on the graphene surfaces using polarized optical microscopy (POM), which yielded colored optical birefringence images of the graphene surface covered with the LC molecules due to molecular interactions between the LC molecules and graphene structures . The color differences in the birefringence images could be readily used to identify the sizes and boundaries of the graphene domains .…”
mentioning
confidence: 99%
“…Techniques [1][2][3][4][5] probing surface-induced order rely on well-aligned mono-or multilayer LC films. Specifically, NMR spectroscopy cannot be applied to thin LC films on planar solid substrates since the number of molecules deposited falls below its required sensitivity level of at least 10 17 molecules.…”
mentioning
confidence: 99%
“…It has been reported that a thin layer of LC molecules on the surface of graphene exhibits significant ππ stacking at the interface, which induces highly ordered packing with respect to each graphene domain. 15,16 Furthermore, the boundaries of these domains could be easily observed under a polarizing optical microscope by exploiting the birefringence of the nematic LC material 12 .…”
Section: -Introductionmentioning
confidence: 99%